NGOs protest US interventions over TRIPS. (1997)
Reports on a letter sent to US Secretary of State in which over 60 international and non-governmental organisations express their concern over the way the US government is interfering in national democratic processes of other nations fashioning their domestic intellectual property laws to conform to international obligations.
DC